2004
DOI: 10.1016/s0017-9310(03)00401-0
|View full text |Cite
|
Sign up to set email alerts
|

Heat and mass transfer in a square microchannel with asymmetric heating

Abstract: This paper describes the heat and mass transfer in a square microchannel that is heated from one side. This microchannel represents a reaction channel in a microreactor that is used to study the kinetics of the catalytic partial oxidation of methane. The microchannel is contained in a silicon wafer and is covered by a thin silicon sheet. At the top side of this sheet, heating elements are present which mimic the heat that is produced as a result of the exothermic chemical reaction. Correlations for Nusselt and… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
29
0
1

Year Published

2004
2004
2018
2018

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 69 publications
(33 citation statements)
references
References 16 publications
3
29
0
1
Order By: Relevance
“…Since the assemblies are made of materials with different conductivities, heat management in narrow spaces and at interfaces is rather complex, and requires special methods for heat addition and removal, such as, for example, an asymmetric introduction of cooling fluid flows. [58][59][60] The small reaction volume of microreactors is also responsible for advantages in their technical safety. [61] The small inner dimensions not only serve to aid heat removal but can also mechanistically control a reaction where, for example, radical chains are terminated such that the nonexplosive region is significantly broader as compared to conventional reactors.…”
Section: Physical Principles For Chemical Processing In Microstructurmentioning
confidence: 99%
“…Since the assemblies are made of materials with different conductivities, heat management in narrow spaces and at interfaces is rather complex, and requires special methods for heat addition and removal, such as, for example, an asymmetric introduction of cooling fluid flows. [58][59][60] The small reaction volume of microreactors is also responsible for advantages in their technical safety. [61] The small inner dimensions not only serve to aid heat removal but can also mechanistically control a reaction where, for example, radical chains are terminated such that the nonexplosive region is significantly broader as compared to conventional reactors.…”
Section: Physical Principles For Chemical Processing In Microstructurmentioning
confidence: 99%
“…Van Male et al already reported that the condition given in Eq. (5) is not always valid for microchannels [29]. For a gas phase reaction in square microchannels with a hydraulic diameter of 500 m, they observed the following Sh correlation:…”
Section: External Mass Transfermentioning
confidence: 99%
“…B. das unsymmetrische Einbringen von Kühlfluidströ-men. [58][59][60] Die sicherheitstechnischen Vorteile von Mikroreaktoren beruhen allerdings nicht nur auf der besseren Wärmeabfuhr in den kleinen Reaktionsvolumina, sondern auch auf ¾nderungen des Reaktionsmechanimus: Beispielsweise werden Kettenreaktionen durch eine Oberflächenreak-tion der Radikale an den Wänden des Mikrokanals unterbrochen (Quenchen), sodass der Nichtexplosionsbereich deutlich größer ist als beim Arbeiten in konventionellen Reaktoren. [40,61,62] Als Folge der laminaren Strömung stellen sich im Kanal typischerweise parabole Geschwindigkeitsprofile ein, die zu breiten Verweilzeitverteilungen führen können.…”
Section: Physikalische Grundlagen Chemischer Prozesse In Mikrostruktuunclassified